Edgardo Pesante: re-construcciones del intelectual santafesino (El Hilo de la Fabula, 2018)
This research is developed within the CAI+D 1 project (in progress) «Selective traditions: trace(s) present and emergent of Italian and french migration of the city of Santa Fe» (FHUC–UNL) and has the object of a first approach to the figure of the writer from Santa Fe Edgardo Pesante as «intellectual», taking into account the complexity that this concept condenses. Departing from this aim, three aspects will be analized: his dimensions as a writer, manager of cultural promotion policies (specifically with regional and young literature) and reviews. This approach (although it is clarified primitive), tries to focus to think not only the boundaries or points of contact with other cultural agents of the province of Santa Fe, but it also indicates the importances of Pesante through the region intellectual field.
Keywords: Edgardo Pesante; intellectual; cultural agent